Competitive influence of purple nutsedge and bermuda grass on cotton cultivar 'AFC-38-12' - Beltrão, Napoleão Esberard de Macêdo; Canuto, Vânia Trindade Barretto; Aguiar, Maria de Jesus Nogueira (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was conducted at Alagoinha, Paraíba, on a sandy and middle fertility soil on 1976. Rainfall during the season was 277,8 mm. The objective of this study was to investigate the competitive influence of purple nutsedge (Cyperus rotunds L.) and bermuda grass (Gynodon dactylon L.) on cotton (Gossypium hirsutum L.) as predominant weeds in the experimental area. The critical period of weed competition on cotton was observed to be the one in which weeds were allowed to grow for 60 days from crop emerging. Cotton with 60 - 75 days of weed-free maintenance was the most productive treatment. Weed competition in the first two months after emerging, reduced cotton productivity by more than 90% in relation to full season weed-free treatment. It reduced also the number of leaves per plant, plant precocity, and plant height, as well as the leaf size, delaying the total crop growth. Besides, the weight of 100 seeds and the weight of one boll were also affected by initial weed competition.